Oxidation resistance and strength retention of laminated G/ZrB2–SiC ceramics. Issue 16 (November 2017) - Wei, Chuncheng; Yu, Changxin; Liu, Xinchao; Ji, Wenyi; Niu, Jinye; Feng, Liu
Abstract: Laminated G/ZrB2 –SiC ceramics were prepared by tap-casting and hot-pressing sintering. The effect of adding ZrB2 and SiC particles into graphite interface layer on the mechanical properties, oxidation resistance and the residual strength after oxidation was investigated. The results showed that the laminated G/ZrB2 –SiC ceramics, with 40 vol% ZrB2 and 10 vol% SiC in the graphite interface layer, had a bending strength of 670 MPa at room temperature and fracture toughness of 13.7 MPa m 1/2 . After oxidation at 1500 °C for 10 h, its bending strength still reached 576 MPa and fracture toughness reached 12.7 MPa m 1/2 . The high retention rate of mechanical properties after oxidation was attributed to the dense SiO2 layer formed on the surface which healed the surface defects and protected effectively the graphite interface layer from oxidation.